A community-based knowledge, attitude and practices study of Accredited Social Health Activist functionaries in active case detection of Leprosy in Sitapur district of Uttar Pradesh - Chaubey, Jaideep Kumar; Neyaz, Arslan; Ahmed, Malik S.; Kumar, Virendra; Nayak, Kripashankar (International Journal of Research in Medical Sciences, 2021)
Background: Leprosy was eliminated at the global level in the year 2000. But regional disparities still exist. Some countries have not attained the elimination status and still reporting a good number of cases. The major burden of new cases was from India, Brazil and Indonesia. Early case detection and treatment is the key to achieve elimination. ASHA workers are involved in this campaign to make it successful. The objective of this study was to assess the knowledge of ASHA functionaries regarding leprosy disease and to analyze the field practices of ASHA functionaries during LCDC activity. Methods: The present study was a community based observational study which was conducted at field practice area of RHTC, Hind Institute of Medical Sciences from 6 November to 19 November 2017. All ASHA functionaries were interviewed using preformed semi-structured questionnaire. Data were stored in Microsoft excel XP and analyzed. Results: None (0%) of ASHA functionaries correctly knew the exact cause of leprosy. Only 10.2% knew mode of transmission, 89.8% knew sign and symptoms, 28.6% knew complications, 12.2% knew prevention of complications, only 10.2% knew exact meaning of MDT. Only 63.3% ASHAs had prior information about orientation training. Out of these only 26.5% completed the practical exercises. Local community remained uninformed about LCDC activity as IEC activities were very poor in all of the centers. Conclusions: In India ASHA workers are the main health functionaries for LCDC activity and in this study, we found that quality of orientation training was substandard as compared to GOI guidelines. So, every effort should be given to make orientation training successful.